Global well-posedness for the fifth order Kadomtsev–Petviashvili II equation in three dimensional space. (January 2016) - Li, Junfeng; Meng, Kun
Abstract: The Cauchy problem for the fifth order Kadomtsev–Petviashvili II equation ∂ x ( ∂ t u − ∂ x 5 u + ∂ x ( u 2 ) ) + △ y z u = 0 is considered. A small data global well-posedness and scattering result in the scale and Galilean invariant space H ̇ − 1 2, 0, 0 ( R 3 ) is derived.